Paintings on the doorway of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
The main doorway that leads to the Bhandasar Temple is decked with various paintings. The pillars are painted white while the Bengal arch roof is painted blue. There is a painting of a Jain Tirthankara on the rectangular slab above the doorway.